Fungsi Tindak Tutur Direktif Wacana Naratif Berisi Dialog dalam Majalah Panjebar Semangat Rubrik Glanggang Remaja: Wacan Bocah - Safira, Isna; Waluyo, Budi; Kurwidaria, Favorita (Universitas Sebelas Maret, 2022)
This research that using pragmatic approach has a purpose to describe the function of directive speech act of Glanggang Remaja: Wacan Bocah rubric. Data analysis technique that used in this study is qualitative inductive analysis technique, through analyzing the directive speech act in accordance to the plot distribution in the narrative discource. The classification of directive speech act in this study refers to Searle's opinion that customized with the plot distribution that proposed by Kosasih. The object that used in this study is narrative discourse of Glanggang Remaja: Wacan Bocah rubric in Panjebar Semangat magazine October – November 2020 edition. The result that obtained from this study are. First, sentence form and function in narrative discourse of Glanggang Remaja: Wacan Bocah rubric that are ask, beg, bid, command, demand, forbid, recommend, and request. Second, based on plot distribution, this study found the use of directive speech act on exposition, complication, rising action, turning point, and ending.